Um Modelo de Agente Econômico Cognitivo com Base no Conceito de Agentes BDI - Jeannes, Fernanda Mendez; Costa, Antônio Carlos da Rocha (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
Social simulations in agent systems have been a constant theme in Artificial Intelligence. This article applies concepts related to microeconomics and microeconomic systems to help the modeling of cognitive economic agents, with consumer and producer behaviors, based on the BDI model of agents.